2018
DOI: 10.1371/journal.pone.0206374
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for developing liver cancer in people with and without liver disease

Abstract: BackgroundThe National Liver Cancer Surveillance Program (NLCSP) targets patients with liver diseases that lead to liver cancer in South Korea. This study aimed to investigate the risk of liver disease leading to liver cancer using nationally representative data to establish an efficient NLCSP.MethodsThis study used data from the National Health Insurance Service National Sample Cohort (NHIS-NSC) from 2002 to 2013. A retrospective matched cohort design was applied to compare the development of liver cancer in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
(23 reference statements)
1
15
0
Order By: Relevance
“…1 HBV and HCV occurred in more than 50% and 25% of HCC patients, respectively. 29 HBV vaccination has been widespread for newborns since 2002 in China. 30 Screening reduces liver cancer incidence and mortality in the Chinese population.…”
Section: Dovepressmentioning
confidence: 99%
“…1 HBV and HCV occurred in more than 50% and 25% of HCC patients, respectively. 29 HBV vaccination has been widespread for newborns since 2002 in China. 30 Screening reduces liver cancer incidence and mortality in the Chinese population.…”
Section: Dovepressmentioning
confidence: 99%
“…Medical Aid beneficiaries are economically and socially vulnerable, and therefore more likely to develop more serious conditions. The liver cancer risk in patients with liver disease was higher among Medical Aid beneficiaries than among National Health Insurance beneficiaries [2]. Medical Aid beneficiaries had a higher suicide rate than National Health Insurance beneficiaries [4].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to National Health Insurance beneficiaries, several studies have reported that Medical Aid beneficiaries had poor health status and received insufficient medical care. Medical Aid beneficiaries showed higher risks of chronic diseases [2, 3] and suicide [4], lower levels of medication adherence and continuity of treatment [5, 6], and lower effectiveness of behavioral intervention programs [7]. They also were more likely to receive lower-quality medical care [8–11], more vulnerable to environmental conditions [12, 13], and less likely to participate in national screening programs [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 75-85% of all liver cancer cases are classified as HCC and 10%-15% of cases are intrahepatic cholangiocarcinoma, according to Global Cancer Statistics 2018 from the International Agency for Research on Cancer. The most common risk factors for HCC are chronic hepatitis B virus (HBV) or hepatitis C virus (HCV) infection, heavy alcohol intake, obesity, type 2 diabetes, and smoking (Lu et al, 2016a;Lu et al, 2016b;Suh et al, 2018). Many studies have revealed that the occurrence and development of HCC are associated with abnormal genetic changes and cancer-related signaling pathways (Koh et al, 2018;Peng et al, 2019;Pinato et al, 2017).…”
Section: Introductionmentioning
confidence: 99%